2016
DOI: 10.1016/j.juro.2016.01.120
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Percent Gleason Grade 4 at Prostate Biopsy in Predicting Prostatectomy Pathology and Recurrence

Abstract: The incremental percentage of Gleason grade 4 disease in biopsy specimens is an important predictor of adverse pathology and biochemical recurrence across the entire range of G4% disease. Accounting for G4% can improve risk assessment even among those patients with Gleason 3+4 or 4+3 cancer and may help inform patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 28 publications
4
73
1
6
Order By: Relevance
“…69 A more recent study that included >1600 patients separated into groups of 10% increases of Gleason pattern 4 in needle biopsies correlates with adverse pathological findings at RP both in patients with Gleason score 3 + 4 = 7 (GrG2) and in those with Gleason score 4 + 3 = 7 (GrG3), and with BCR. 70 A separate study that included >1200 patients also divided the patients into groups with increasing percentages of Gleason pattern 4, and found that a higher percentage of Gleason pattern 4 predicts EPE at RP. 71 Therefore, as more studies are being performed, it is possible that the percentage of Gleason pattern 4 will be included in prediction models for significant cancer.…”
Section: T U M O U R G R a D E A T N E E D L E B I O P S Y A S A P R mentioning
confidence: 99%
“…69 A more recent study that included >1600 patients separated into groups of 10% increases of Gleason pattern 4 in needle biopsies correlates with adverse pathological findings at RP both in patients with Gleason score 3 + 4 = 7 (GrG2) and in those with Gleason score 4 + 3 = 7 (GrG3), and with BCR. 70 A separate study that included >1200 patients also divided the patients into groups with increasing percentages of Gleason pattern 4, and found that a higher percentage of Gleason pattern 4 predicts EPE at RP. 71 Therefore, as more studies are being performed, it is possible that the percentage of Gleason pattern 4 will be included in prediction models for significant cancer.…”
Section: T U M O U R G R a D E A T N E E D L E B I O P S Y A S A P R mentioning
confidence: 99%
“…Further, a global Gleason score is generally reported taking into account the grade patterns of the carcinoma foci encountered in all cores. Although it may seem counterintuitive, three recent studies showed that the global Gleason score outperformed the ‘worst’ Gleason score with regard to pathological features in corresponding prostatectomy specimens …”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
“…Subsequent studies on quantitative grading showed the incremental, rather than acute, increase in risk of biochemical recurrence at higher proportions of the grade 4 component. It is thought that quantitative grading might limit the clinical impact of interobserver variation regarding borderline findings such as tumours with, for instance, very small Gleason grade 4 fractions impacting a man's eligibility for active surveillance . One study reported that interobserver reproducibility of percent Gleason grades 4 or 5 on prostate biopsies is at least as good as that of Gleason score .…”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an exceptionally large cohort of 12 823 consecutive patients and of 2971 matched preoperative biopsies was used to validate the importance of assigning the percentage of Gleason pattern 4 and 5 with biochemical relapse . This has been validated in a number of other studies, and it has been suggested, for instance, that the percentage of grade 4 may be used to determine criteria for active surveillance in those with minimal grade 4 disease …”
Section: Introductionmentioning
confidence: 99%